Succession pattern of cadaverous entomofauna in a semi-rural area of Bogotá, Colombia (2009)
The main objective of this work was to examine the succession of insects colonizing three pig (Sus scrofa) cadavers in a semi-rural area of Bogotá. The 12 kg pigs were shot and put into metallic mesh cages to allow access by insects. Arthropods were then sampled at different intervals depending on the corresponding stage of decomposition. In total 5981 arthropods were collected during decomposition, 3382 adults and 2599 immature stages, belonging to 10 orders and 27 families. Sarconesia magellanica and Compsomyiops verena (Diptera: Calliphoridae) were the first species to colonize the corpses. Egg masses and 1st stage Calliphoridae larvae were associated with the fresh stage of decomposition, 1st and 2nd stage larvae of Calliphoridae and Sarcophagidae during chromatic and emphysematous stages, immature Chrysomya albiceps (Diptera: Calliphoridae), Ophyra sp. (Diptera: Muscidae) and Oxellytrum discicolle (Coleoptera: Silphidae) during the colliquative stage and mainly Coleoptera during the skeletization phase (plus some adult Diptera). The data obtained in the present investigation could be used for the estimation of postmortem interval (PMI) in real cases when the conditions to which a cadaver has been exposed are similar to those recorded during this work. © 2009 Elsevier Ireland Ltd. All rights reserved.